UPAYA PERLINDUNGAN KORBAN TINDAK PIDANA PERKOSAAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Akbar Sayudi (Universitas Lampung, 2016)
The importance of the protection of victims of crime to obtain serious attention, it can be seen from one form of protection by the state is the administration of justice. In addition completeness of legislations, witness and victim protection agency (LPSK), law enforcement agencies, relevant government agencies, and other parties relevant, then the judicial function plays an important role. The function of the court not only making verdict, but also recept report of compensation, or restitution, announce it and ordered the agency or the parties to implement the decision and so on. By applying legal sanctions to the perpetrator, then it implies that it is a form of attention (protection) judicially to victims of crime. Legal protection to women who are victims of this crime is not just limited to the penalization to the perpetrators, but also to the consequences that happened to him, like a pregnancy caused by rape. Keywords: Protection, Victim, Rape